Hair: An Evidence for Drug of Abuse (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
Hair analysis for drug abuse has been gaining increasing significance in forensic sciences. Hair is a special evidence used for the investigation of chronic drug of abuse or poisoning in criminal cases. It provides results with sensitive methods even if the drug is present in low amount. Segmental hair analysis can yield information about the time course of the substance used. Forensic hair analysis generally involves cases where the drug history of an individual is required. The hair analysis has to be undertaken by a specialist forensic toxicologist and the test is sometimes referred to as a ‘hair follicle test’. Apart from collecting samples of hair for analysis, the forensic group involves an internationally recognized specialist forensic hair toxicologist who reviews work already completed by other forensic hair toxicologists. The hair sampling, sample preparation, and analytical performance are very important for final results. The outcomes of hair analysis have been reviewed by dividing the drugs into six groups: opiates, cocaine, amphetamines, cannabinoids, abused therapeutic drugs, and the markers of chronic alcohol consumption.
Keywords: Segmental hair; therapeutic drugs